Fifty years of training professionals in Library Science at the University of Costa Rica (UCR) - Sandí Sandi, Magda Cecilia (2018)
Describes the historical background of the creation of the career of Librarianship at the University of Costa Rica (UCR), a pioneering university in training professionals in this discipline. In the 1950s, training activities were intensified to train personnel to technically organize the libraries that were being consolidated in the country, such as the National Library, the University of Costa Rica Library and school libraries. To this end, the development of professional activities was sponsored by international organizations such as the OAS, IICA and UNESCO.